1958
DOI: 10.1122/1.548829
|View full text |Cite
|
Sign up to set email alerts
|

The Creep of Snow under Combined Stress

Abstract: Unclassified Report Laboratory experiments on the creep of sifted snow under uniaxial, hydrostatic, and confined-side compressive stresses are described, and the re sults are discussed on the basis of an additive theory for combined stresses. Stress (4-40 psi) and temperature (-3.6C to-13.6C) dependence was investigated for 35 samples (initial density =0.4 g/ cm3) subjected to uniaxial and hydrostatic stress for 200-sec time increments. Another series of 104 samples (initial densities 0.36-0.63) was subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1964
1964
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…In order to assess the influence of a and b on the simulation, another set of functions, noted a2 and b 2 , was obtained by analysing the experimental results of Landauer (1957) through Duva and Crow's (1994) modeL Landauer performed a number of creep tests on snow, under isotropic compression, uniaxial compression and compression with lateral confinement, and found that for relative densities D between 0.39 and 0.69, and loads between 0.027 and 0.27 MPa, the appropriate value of exponent n was 3. The corresponding values of a and b are shown in Figure 2a and b, as well as the continuous set of functions which fit these values, given by:…”
Section: 'Yementioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the influence of a and b on the simulation, another set of functions, noted a2 and b 2 , was obtained by analysing the experimental results of Landauer (1957) through Duva and Crow's (1994) modeL Landauer performed a number of creep tests on snow, under isotropic compression, uniaxial compression and compression with lateral confinement, and found that for relative densities D between 0.39 and 0.69, and loads between 0.027 and 0.27 MPa, the appropriate value of exponent n was 3. The corresponding values of a and b are shown in Figure 2a and b, as well as the continuous set of functions which fit these values, given by:…”
Section: 'Yementioning
confidence: 99%
“…Model parameters a (a) and b (b) vs relative density D. Solid lines showDuva and Crow's (1994) originalfunctions (ao, bo), andfunctions(aI, bIJ, (a2, b 2 ) used in this study. Symbols show the values corresponding to Site 2 data and toLandauer's (1957) creep tests (u, uniaxial compression; C, confined compression; 1, isotropic compression).…”
mentioning
confidence: 99%
“…In this case obviously only the first of the above-mentioned methods will furnish reliable results. Landauer (1957) first recognized that the cross-section numbers resulting from the second method and the use of Equation (6) generally over-estimates the real coefficients ζ . His results using method 1 and 2 are represented in Figure 8.…”
Section: Snow Cover On Horizontal Groundmentioning
confidence: 99%
“…However to characterize it is often very difficult. Density and temperature may be of considerable influence, but cannot give a good indication of the state of the bond system, and for this reason results which did not consider the bond system differ widely (Landauer, 1957; Yosida and others, 1955–58; Ramseier and Pavlak, 1964; Feldt and Ballard, 1965; Ballard and Feldt, 1965; Kinosita, 1967; Shinojima, 1967; Mellor and Smith, 1967; Keeler, 1969; Yong and Fukue, 1977).…”
Section: Introductionmentioning
confidence: 99%